2021
DOI: 10.21203/rs.3.rs-335885/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overabundance of Asaia and Serratia bacteria is associated with deltamethrin insecticide susceptibility in Anopheles coluzzii from Agboville, Côte d’Ivoire

Abstract: Background Insecticide resistance among mosquito species is now a pervasive phenomenon, which threatens to jeopardise global malaria vector control efforts. Evidence of links between the mosquito microbiota and insecticide resistance is emerging, with significant enrichment of insecticide degrading bacteria and enzymes in resistant populations. Using 16S rRNA amplicon sequencing, we characterised and compared the microbiota of Anopheles (An.) coluzzii in relation to their deltamethrin resistance and exposure p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…crowding, access to nutrition) 40 , time of testing (e.g. night or day) 41,42 , temperature and humidity 43 , mosquito age 44 and physiological status 45 can have a significant effect on observed bioassay mortality. Whilst every effort is made to maintain standardized test conditions, according to WHO protocols 30 , even differences of 4 °C during holding periods can have a significant effect on mosquito mortality 43 , with lower temperatures associated with reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…crowding, access to nutrition) 40 , time of testing (e.g. night or day) 41,42 , temperature and humidity 43 , mosquito age 44 and physiological status 45 can have a significant effect on observed bioassay mortality. Whilst every effort is made to maintain standardized test conditions, according to WHO protocols 30 , even differences of 4 °C during holding periods can have a significant effect on mosquito mortality 43 , with lower temperatures associated with reduced mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic resistance resulting from enhanced detoxi cation of insecticides has been reported as the cause of resistance to insecticides from diverse classes and are usually associated with over-expression of detoxi cation enzymes 26 . Other mechanisms of insecticide resistance identi ed include mosquito microbiome components and cuticle alterations [26][27][28][29] . Resistance to several insecticides of all major classes has been reported in An.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, plant diet could change the microbiota composition of mosquito females 59,60 , which in turn could modify mosquito response to deltamethrin [61][62][63][64] . Our results showed that mosquito KD rate and mortality varied among the two replicates.…”
Section: Discussionmentioning
confidence: 99%